1967
DOI: 10.1530/jrf.0.0140071
|View full text |Cite
|
Sign up to set email alerts
|

Use of Probit Analysis in a Study of the Effect of the Ram on Time of Ovulation in the Ewe

Abstract: To investigate the relationship between oestrus and time of ovulation from the start of heat and the effect of the ram on this relationship, 200 ewes, half of which had been run with rams continuously during oestrus, were slaughtered at intervals after the end of heat. The method of probit analysis was used to fit multiple regression equations for percentage of ewes ovulated (as a probit) in terms of slaughter time and heat length. From these equations, estimates of mean ovulation times for various heat length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

1967
1967
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…An experiment to determine the effect of the continuous presence of rams on the time of ovulation in the ewe is reported separately (Parsons, Hunter & Rayner, 1967).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An experiment to determine the effect of the continuous presence of rams on the time of ovulation in the ewe is reported separately (Parsons, Hunter & Rayner, 1967).…”
Section: Methodsmentioning
confidence: 99%
“…McKenzie & Terrill (1937) reported that intermittent, sterile copulation 3, 12 and 24 hr after the onset of oestrus tended to shorten its duration. Records at the Department of Animal Science (Hunter, 1964) (Parsons, 1965) (1961) found that ewes showed no apparent preference when allowed free choice of rams, Young (1941) length through the reluctance of teaser rams to mount recently mated ewes (Pepelko & Clegg, 1964), the criterion used in all the experiments to determine the end of oestrus was based on the ewes' reactions to rams exhibiting high libido. For this purpose, intensity of oestrus was graded at each teasing period (see Table 1) and when a ewe appeared to be going off heat she was teased with at least three highly active rams.…”
Section: Introductionmentioning
confidence: 99%
“…
Mating has been shown to have effects on ovulation in a number of species which ovulate spontaneously, such as rats (Aron, Asch & Asch, 1961; Aron, Asch & Ross, 1966; Zarrow & Clark, 1968) and sheep (Parsons, Hunter & Rayner, 1967; Van der Westhuysen, Van Niekerk & Hunter, 1970). In the sow, the results obtained by Pitkjanen (1955) and Lebedev (1957) Fifty-nine Large White gilts were mated at the time of the second oestrus following withdrawal of methallibure (I.C.I.
…”
mentioning
confidence: 99%
“…L'activité sexuelle elle-même n'est pas en cause puisque l'effet est le même si le contact n'a lieu que pendant les 24 h suivant l'injection d'oestrogènes c'est-à-dire avant que n'apparaisse la réceptivité sexuelle de la femelle. Le contact physique n'est pas nécessaire mais le canal sensoriel olfactif n'est pas seul en cause : des brebis anosmiques réagissent comme des témoins lorsqu'elles sont en présence du mâle (Signoret et Rayner, 1967 ;Cahill et al, 1974). La maîtrise, grâce à un traitement de progestagènes, des processus qui conduisent à l'ovulaiion (Robinson, 1965 ;Cognié, Mariana, Thimonier, 1970) (Lindsay et al,1975).…”
unclassified